Development of STEAM-Based Student Worksheets on Thermochemistry Topic: Validity and Practicality Analysis - Widiastuti, Nabila Lailil; Solfarina, Solfarina; Aisyah, Ratna Sari Siti; Namirah, Irah; Wijayanti, Imas Eva (Universitas Lambung Mangkurat, 2026)
This development research produces teaching materials in the form of students' worksheet on thermochemical materials. The results of the development of students' worksheet that have been designed are tested for validity and practicality to qualify the requirements of a students' worksheet. This development research of students' worksheet uses the R&D (Research and Development) method, namely with the ADDIE model. This ADDIE model has 5 stages, namely: (1) analyze, (2) design, (3) develop (4) implement and (5) evaluate. In this study, the instrument used was questionnaire of student needs analysis, validation questionnaire of topic and language expert, validation questionnaire of and media expert and practicality questionnaire. Validation is conducted by 6 validators, consisting of 3 topic experts and 3 language experts. Practicality test is conducted by students of grade XI. Test of students' worksheet will be analyzed using Aiken's formula. Based on the results of the analysis, it can be stated that the resulting students' worksheet is a teaching materials product that is categorized as valid based on the V value from Aiken's. The conclusion of this development research has produced teaching materials in the form of student worksheet integrated with STEAM (Science, Technology, Engineering, Art and Mathematics) on Thermochemistry material using the ADDIE model. The student worksheet as teaching materials has received a valid category and a practicality level that is implemented by students of 84% with component details are content 0,86, language 0,83, presentation 0,84 and graphical 0,84.